An SEM study of the effects of different irrigation sequences and ultrasonics - Abbott, P V; Heijkoop, P S; Cardaci, S C; Hume, W R; Heithersay, G S (International endodontic journal, 1991)
The root canals of 30 extracted human teeth with single canals were prepared biomechanically with hand instruments using a flaring technique. Three different irrigation regimes were used, with and without ultrasonic activation of a root canal file. The six irrigation sequences used in this study were as follows: Savlon, Savlon with ultrasound, EDTAC/NaOCl/EDTAC, EDTAC/NaOCl/EDTAC with ultrasound, NaOCl/EDTAC/NaOCl, and NaOCl/EDTAC/NaOCl with ultrasound. Scanning electron microscopic (SEM) examination of the prepared root canal walls showed a complete smear layer when Savlon was used. Ultrasound reduced the amount of smear with Savlon, but did not do so significantly with the other irrigation regimes. The most effective irrigation regime for removing smear layer and other debris was EDTAC/NaOCl/EDTAC. In all groups there was a significant decrease in cleaning efficiency as the apical end of the canal was approached.